EXPERIMENTAL AND NUMERICAL STUDY OF ENHANCEMENT HEAT TRANSFER COEFFICIENT IN SPIRAL FLUTED TUBE HEAT EXCHANGER WITH NANOFLUID - S. Kassim, Muna; A. Saleh, Fouad; O.Samarmad , Ahmed (Journal of Engineering and Sustainable Development, 2015)
The experimental and numerical investigation has been performed in this work to study the enhancement of heat transfer coefficient in a spiral fluted tube heat exchanger with Nanofluid. The shell side was made from a galvanized tube of (65 mm) outer diameter. The tube was made from copper material of (1000 mm) length having (16 mm) equivalent inner diameter and (17 mm) outer diameter, it was inserted inside the shell. Steam was used, as a heating source where constant wall temperature condition (110˚oC) was achieved, and TiO2 /water nanofluid with various volume concentrations (0.08%, 0.1%, 0.2%, and 0.3%) by volume at Reynolds numbers (7000 to 15000) has been employed, as working fluid flows through the inner tube. Fiberglass has been utilized to cover the outer surface of the shell for reducing heat losses. The performance of a spiral fluted tube heat exchanger with and without nanofluid was investigated experimentally. Experimental results reveal that the use of a spiral fluted tube without nanofluid leads to an increase (28-33) % in heat transfer coefficient compared with a smooth tube, and the maximum increase in heat transfer coefficient occurs when using a spiral fluted tube with nanofluid at 0.3% volume concentration was about (25-28) % higher than the pure water in spiral fluted tube. Empirical correlations for water and nanofluid were represented by the Nusselt number. Numerical simulation has been carried out on the present heat exchanger to analyze both flow field and heat transfer using ANSYS 14, FLUENT package...